THE EUROPEAN MONETARY INTEGRATION TRAP: INCOMPLETE SOVEREIGNTY AND THE STATE-MIMICKING METHOD - CABRAL, Nazaré da Costa (Theoretical and Practical Research in Economic Fields; Vol 13 No 2 (2022): TPREF, Volume XIII, Issue 2(26), Winter 2022DO - 10.14505/tpref.v13.2(26).06, 2022)
The author identifies the two main (external and internal) dimensions of incomplete sovereignty in the EMU and the respective caveats affecting the scope of the single monetary policy, here described as a ‘monetary policy integration trap’. The author details the main implications caused by this curtailed sovereignty both in its external and internal dimensions – e.g. on the one hand, the polarisation of external positions and, on the other hand, the effects of limited European fiscal/budgetary sovereignty and the atypical interaction between the latter and the single monetary policy. Finally, the way the E(M)U has in recent years addressed this integration trap is analysed, making use of a heterodox method here labelled as the ‘State-mimicking’ method. The main conclusion is that such a method is the possible yet imperfect policy solution to bypass the monetary policy integration trap, given the E(M)U’s ontological ambiguities - a quasi-State afraid to become one.